Effects of periodic carbohydrate ingestion on endurance and cognitive performances during a 40-km cycling time-trial under normobaric hypoxia in well-trained triathletes - Liao, Y.-H.; Mündel, T.; Yang, Y.-T.; Wei, C.-C.; Tsai, S.-C. (Journal of Sports Sciences, 2019)
The purpose of this study was to examine CHO ingestion on a cognitive task using a field-simulated time-trial (TT) under hypoxia in well-trained triathletes. Ten male triathletes (age: 22.1 ± 1.1 years; VO2max: 59.4 ± 1.4 ml/kg/min) participated in this double-blind/crossover/counter-balanced design study. Participants completed 3 TT trials: 1) normoxic placebo (NPLA; FiO2 = 20.9%), 2) hypoxic placebo (HPLA; FiO2 = 16.3%), and 3) hypoxic CHO (HCHO; 6% CHO provided as 2 ml/kg/15 min; FiO2 = 16.3%). During the TT, physiological responses (SpO2, HR, RPE, and blood glucose/lactate), cognitive performance, and cerebral haemodynamics were measured. Hypoxia reduced TT performance by ~3.5-4% (p < 0.05), but CHO did not affect TT performance under hypoxia. For the cognitive task, CHO slightly preserved exercise-induced cognitive reaction speed but did not affect response accuracy during hypoxic exercise. However, CHO did not preserve the decreased Hb-Diff (cerebral blood flow, CBF) and increased HHb in the prefrontal lobe (p < 0.05) during hypoxic exercise, and CHO failed to preserve hypoxia-suppressed prefrontal CBF and tissue oxygen saturation. In conclusion, the present study demonstrates that CHO is effective in sustaining reaction speed for a cognitive task but not promoting TT performance during hypoxic exercise, which would be important for strategy-/decision-making when athletes compete at moderate high-altitude.